EFFECT OF PRODUCTION COSTS, AND DISTRIBUTION COSTS ON TURNOVER SALES (Case Study aat PT Sandana Istana Multigas) - Dumadi Dumadi; Sugiani Sugiani; Anisa Sains Kharisma; Nur Afrida; Hilda Kumala Wulandari (SEAN Institute, 2023)
This study aims to determine and analyze the effect of production costs and distribution costs on sales turnover at PT Sandana Istana Multigas. This study used secondary data. The population in this study is bookkeeping related to production costs, distribution costs and sales turnover at PT Sandana Istana Multigas, Tegal City. The sample in this study is the bookkeeping report of PT Sandana Istana Multigas for the period 2017 to 2019. Hypothesis testing uses descriptive analysis, normality test, heterochedasticity test, multicholinearity test, and multiple regression test. Data analysis is assisted with the SPSS application. The results of this study show that production costs have a negative and significant effect on sales turnover, distribution costs have a positive and significant effect on sales turnover, production costs and distribution costs simultaneously have a positive and significant effect on sales turnover.